2000
DOI: 10.1021/ma0010534
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-Catalyzed Enantioselective Copolymerization of Substituted Lactones to Optically Active Polyesters

Abstract: Enantioselective copolymerization of racemic substituted lactones with achiral lactones has been examined by using Candida antarctica lipase as catalyst. In the copolymerization of racemic β-butyrolactone with 12-dodecanolide, the (S)-isomer was preferentially reacted to give the (S)-enriched optically active copolymer with enantiomeric excess of β-butyrolactone unit = 69%, which is much larger than that of the homopolymerization under similar reaction conditions. The absolute configuration of β-butyrolactone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…remained unreacted. This indicated that the S-isomer of β-BL preferentially reacted during the copolymerization (Scheme 16a) [114]. Also, during the copolymerization of the racemic β-BL with DDL, the (S)-isomer of β-BL preferentially reacted to give the (S)-enriched optically active copolymer with an enantiomeric excess of the β-BL unit of 69%, which is much higher than that for the homopolymerization of β-BL.…”
Section: (R S)-4-mecl] and 4-ethyl-caprolactone [(R S)-4-etcl]mentioning
confidence: 98%
“…remained unreacted. This indicated that the S-isomer of β-BL preferentially reacted during the copolymerization (Scheme 16a) [114]. Also, during the copolymerization of the racemic β-BL with DDL, the (S)-isomer of β-BL preferentially reacted to give the (S)-enriched optically active copolymer with an enantiomeric excess of the β-BL unit of 69%, which is much higher than that for the homopolymerization of β-BL.…”
Section: (R S)-4-mecl] and 4-ethyl-caprolactone [(R S)-4-etcl]mentioning
confidence: 98%
“…Almost all polymerization reactions were conducted in organic solvents, such as: toluene [40], 1,4-dioxane [41], isopropyl ether [42], isooctane [43], diphenyl ether [44], cyclohexane [45]. The reaction was also carried out in supercritical carbon dioxide [46,47], ionic liquids [48][49][50], and recently, in aqueous dispersion [51].…”
Section: Linear and Star Ester Oligomersmentioning
confidence: 99%
“…The higher polymerizability was reached during enantioselective copolymerization of β-BL with ε-CL or 12-dodecanolide, where the final product was characterized by M n about 1.7 and 2.3 kg mol −1 , respectively. Moreover, it was proved, that the (S)-isomer of β-BL is Scheme 2 Reaction pathway for synthesis of cyclic carbonate by lipase catalyzed reaction and thermal cyclization more readily polymerizable than the (R)-isomer to give the copolymer with relatively high optical purity in the (S)-enriched form [43].…”
Section: Linear and Star Ester Oligomersmentioning
confidence: 99%
“…2-9 Enantio-and regioselective polymerizations have been achieved via lipase catalysis to give functional polyesters, most of which can not be synthesized by conventional chemical catalysts. [10][11][12][13][14][15] Candida antarctica lipase (lipase CA) immobilized on macroporous acrylic resin (Novozym 435) is industrially developed for modification of triglyceride oils. Previously, we first demonstrated highly efficient catalysis of Novozym 435 for polymerization of lactones; 16 a small amount of this enzyme (less than 1%) induced the polymerization of ε-caprolactone (ε-CL) and the polymerization rate using Novozym 435 was much larger than that by other commercially available lipases under the similar reaction conditions.…”
mentioning
confidence: 99%